Characterisation and modelling of static recovery process of Aluminium-copper alloy - Mohd Hosni, Ismail (2008)
The main objective of this project is to determine the activation energy of aluminium-copper alloy using interrupted of tensile test procedure. The interrupted process was conduct at recovery stage, which is to investigate effect of recovery due to influence of pre-strain. The process of recovery is to relieve the internal residual stresses during cold work. The specimens were tested at variable pre strain (2.5%, 5%, 7.5%, 10%.), temperature (100 °C, 150 °C, 200 °C and 250 °C) and at different annealing time (1 hour, 2 hour, 3 hour and 4 hour). The specimens were machining using lathe machine from larger stock before go to the annealing process. The process of annealing was carried out using box furnace by holding the specimens at an elevated temperature. After the annealing process, the specimens were tested using tensile test machine. This process is required to find the value of yield stress of undeformed material, deformed and at static recovery condition. The value of yield stress depends on the condition of the annealing process. From the data of yield stress, the graph of the Xrec (degree of recovery) versus pre-strain, temperature and time can be plot. By using linear line equation of the graph, the activation energy can be calculate by implement the equation of Friedel's model. The value of activation energy depends on the value of the temperature and time that has been used. From the experiment, the value of activation energy at variable temperature is 630 kJ/mol and for the variable time is 211 kJ/mol. From the data of the research it can be use to validate the equation of Friedel's model by make a comparison between the value of activation energy with the data from the journal.